Algoritma Extended Weighted Tree Similarity untuk Memberikan Solusi Memasak pada J2ME - Yosephine, Halim; Ramos, Somya; Charitas, Fibriani (d'CARTESIAN:Jurnal Matematika dan Aplikasi, 2012)
Abstract The aim of this thesis is to give the simplicity in cooking with limited ingredients for the users by using mobile technology (J2ME). The aim of this thesis can be done by using Extended Weighted Tree Similarity Algorithm, a calculation to find out the highest weight similarity between the menu which has been inputted in the application as a database; and the inputted ingredients from the users of this application. The conclusion of this thesis is that Algorithm Extended Weighted Tree Similarity can be implemented into mobile technology (J2ME).  Keywords: extended weighted tree similarity, cooking smart, J2ME Abstrak Tujuan dari penelit ian ini adalah   memberikan kemudahan dalam memasak dengan bahan yang terbatas bagi pengguna  dengan menggunakan  teknologi  mobile  (J2ME).  Tujuan dari  tesis ini  dapat dilakukan dengan menggunakan  Algoritma  Extended Weighted Tree Similarity, perhitungan  untuk mengetahui  kesamaan  bobot  tertinggi antara menu  yang telah  diinput  dalam aplikasi  sebagai  database, dan  bahan-bahan  dimasukkan  dari  pengguna  aplikasi ini.  Kesimpulan dari  tesis ini  adalah bahwa  Algoritma Extended Weighted Tree Similarity dapat diimplementasikan ke dalam teknologi mobile (J2ME).  Kata Kunci : extended weighted tree similarity, cooking smart, J2ME